2013
DOI: 10.1002/jhet.1897
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of the Synthesis of Ketanserin (5) and its Hydrochloride Salt (5.HCl) via 3‐(2‐Chloroethyl)‐2,4‐(1H,3H)‐quinazolinedione (2) or Dihydro‐5H‐oxazole(2,3‐b)quinazolin‐5‐one (1)

Abstract: The synthesis of ketanserin (5) and its hydrochloride salt (5.HCl) using respectively equimolar amounts of 3‐(2‐chloroethyl)‐2,4‐(1H,3H)‐quinazolinedione (2) with 4‐(parafluorobenzoyl)piperidine (3) and dihydro‐5H‐oxazole(2,3‐b)quinazolin‐5‐one (1) with hydrochloride salt of 4‐(parafluorobenzoyl)piperidine (3.HCl) is reinvestigated. The one‐pot reaction of ethyl‐2‐aminobenzoate with ethyl chloroformate and ethanol amine has afforded 3‐(2‐chloroethyl)‐2,4‐(1H,3H)‐quinazolinedione (2) (86%) that was then refluxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The higher energy (and thus less stability) in the latter complex-16 may be attributed to the unfavorable steric interaction between the tert-butyl group and the 3OH-Quiz chelates (1)(2)(3) in view of the C-H to N-O vDW repulsion. This weakness explains why the reaction time was much longer and in a range of 50 h to 4-5 days (cf 30 h to 2-3.5 days by using 3-DMP catalyst).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher energy (and thus less stability) in the latter complex-16 may be attributed to the unfavorable steric interaction between the tert-butyl group and the 3OH-Quiz chelates (1)(2)(3) in view of the C-H to N-O vDW repulsion. This weakness explains why the reaction time was much longer and in a range of 50 h to 4-5 days (cf 30 h to 2-3.5 days by using 3-DMP catalyst).…”
Section: Discussionmentioning
confidence: 99%
“…Quinazolin-4-ones and -2,4-diones (Quizones) have been well documented as an important template of potential pharmacological and biochemical interests. Relevant studies of Ketanserin in these areas have strongly suggested that these derivatives can be used for treating hypertensive symptoms by reducing peripheral vascular resistance by blocking the effect of serotonin functions (Figure 1) [1,2]. In addition, an amide variant TCMDC-125133 bearing a chiral α-Quizone group was found to exhibit effective antimalarial activity against the Plasmodium falciparum 3D7 strain (Figure 1) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Quinazolinediones are an important class of nitrogen-containing heterocycles in medicinal chemistry with a broad range of bioactivities, such as antihypertensive, , antidiabetic, antimicrobial, , antimalarial, , and anticancer activities. Structures shown in Figure are representative examples of commercial drugs or biologically active compounds and natural products containing the quinazoline-2,4-dione core. Among them, Zenarestat is a therapeutic agent against diabetic neuropathy. Due to the importance of quinazoline-2,4-diones in medicinal chemistry, various synthetic methods have been reported to construct this core. The representative strategies for the construction of quinazoline-2,4-diones have been summarized in the introduction part of our previous article .…”
Section: Introductionmentioning
confidence: 99%
“…Quinazoline-2,4­(1 H ,3 H )-diones are important building blocks for the production of various bioactive compounds and commercial drugs, such as linagliptin, sotrastaurin, tioperidone, nitraquazone, and ketanserin, containing at least one quinazoline moiety. The traditional approach employed to produce this important class of compounds usually utilized phosgene and related agents, which have the disadvantages of requiring toxic reagents and multistep procedures.…”
mentioning
confidence: 99%
“…The results are represented in Scheme A. The antihypertensive drug pelanserin ( 2ap ) was easily synthesized in 99% yield within 2 h. Cloperidone ( 2aq ) and ketanserin ( 2ar ), also antihypertensive drugs, were produced in 96% and 94% yields in 4 h, respectively. It is important to mention that many important drugs containing quinazolinedione skeletons have differential substituents on the N 1- and N 3-positions, which generally cannot be selectively embedded.…”
mentioning
confidence: 99%